Is Our History Bunk? Adult Education’s Historiography and the Notion of "Learning Society" - John Holford (Adult Education Research Conference, 1998)
The notion of "learning society" presents a paradigm shift necessitating radical rethought of approaches to historical research in adult education. This paper re-evaluates the English-language historiography of adult education from a "learning society" perspective.